The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1021/acs.jnatprod.4c00008
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Antibacterial Evaluation of Lupinifolin and Its Natural Analogues

Hongbo Dong,
Li Liao,
Bin Long
et al.

Abstract: In this study, lupinifolin (1) and its natural analogues, mundulin (2), minimiorin (3), khonklonginol H (4), flemichin D (5), and eriosemaone A ( 27), were obtained by chemical synthesis for the first time. Key steps involved an electrocyclization to build the linear pyran rings and a Claisen/ Cope rearrangement to install the 8-prenyl substituents. All compounds were assessed for their in vitro antimicrobial activities against clinically relevant human pathogens, including one Gramnegative bacterial strain (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Aromatic Claisen rearrangement or cyclization in DMF afforded 20 as the main product (77%, entry 3), while in xylene, 19 was isolated as the main product in a yield of 55% (entry 4). We then found that the addition of KOH to xylene could effectively control the regioselectivity, and pure 19 was obtained in 93% yield (entry 5) [33,35], whereas the reported Claisen rearrangement/cyclization conditions of 15 only yielded a roughly 1:1 mixture of 19 and 20 under harsh conditions (entry 6) [23]. As shown in Table 2, the synthesis of scandenone (1) and osajin (2) commenced with the stereocontrolled preparations of tetracyclic isoflavens 19 and 20, which possessed a linear or angular pyran attached to the A-ring, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Aromatic Claisen rearrangement or cyclization in DMF afforded 20 as the main product (77%, entry 3), while in xylene, 19 was isolated as the main product in a yield of 55% (entry 4). We then found that the addition of KOH to xylene could effectively control the regioselectivity, and pure 19 was obtained in 93% yield (entry 5) [33,35], whereas the reported Claisen rearrangement/cyclization conditions of 15 only yielded a roughly 1:1 mixture of 19 and 20 under harsh conditions (entry 6) [23]. As shown in Table 2, the synthesis of scandenone (1) and osajin (2) commenced with the stereocontrolled preparations of tetracyclic isoflavens 19 and 20, which possessed a linear or angular pyran attached to the A-ring, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The MIC of natural compound 2 against S. aureus ATCC29213 was 2 The target compounds (1-3) were evaluated for their in vitro antibacterial activities against three Gram-positive (G+) bacterial strains (S. aureus ATCC29213, MRSA ATCC33591, and Enterococcus faecalis ATCC29212,) and one Gram-negative (G-) bacterial strain (E. coli ATCC25922) using minimum inhibitory concentration (MIC) values. Ampicillin and vancomycin were used as the positive controls [33].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations